Analysis of Data Security Improvement with the 12x8 Matrix Cipher Playfair Algorithm - sipayung, Liskedame Yanti; Siahaan, R. Fanry; Lubis, Rodiah Hanum; Amalia, Dwi Novia (Bahasa Indonesia, 2025)
This research proposes a modification of the Playfair Cipher algorithm with a 12×8 matrix to improve data security. This method expands the key space to 96 by adding characters (letters, numbers, symbols), thereby increasing resistance to brute-force attacks and frequency analysis. Test results show that the resulting ciphertext has high entropy with an even character distribution, and an average encryption time of 0.15 seconds per 1,000 characters. Security analysis proves that the 12×8 matrix requires >10¹⁰⁰ years to be computationally cracked, significantly more secure than the 5×5 matrix. Despite the higher resource requirements, this algorithm remains efficient for applications such as sensitive data storage and encrypted communications. In conclusion, this modification offers significant security improvements without drastically sacrificing performance.